2019
DOI: 10.1039/c9ja00174c
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for recovering and preconcentrating mercury in natural water samples for stable isotope analysis

Abstract: A new method is developed to meet the criteria for precise and efficient measurements of mercury isotopic composition in various water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 41 publications
4
44
0
Order By: Relevance
“…Thus, we chose the big leaf poplar, common sea buckthorn, and willow grown at the site of 1958 and Faber's fir and dragon spruce grown at the site of 1930 to measure the Hg isotopic signatures. Precipitation and throughfall samples collected during September−November 2017 were analyzed by the Hg isotopic signatures, following the method described by Li et al 42 More details can be found in Section S4 of the Supporting Information. Briefly, 5 L of water (about 10−35 ng Hg) was collected by a precipitation collector and filtered through cellulose membranes with 0.45 μm pore size.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we chose the big leaf poplar, common sea buckthorn, and willow grown at the site of 1958 and Faber's fir and dragon spruce grown at the site of 1930 to measure the Hg isotopic signatures. Precipitation and throughfall samples collected during September−November 2017 were analyzed by the Hg isotopic signatures, following the method described by Li et al 42 More details can be found in Section S4 of the Supporting Information. Briefly, 5 L of water (about 10−35 ng Hg) was collected by a precipitation collector and filtered through cellulose membranes with 0.45 μm pore size.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 5 L of water (about 10−35 ng Hg) was collected by a precipitation collector and filtered through cellulose membranes with 0.45 μm pore size. Variable volumes (5−20 mL) of BrCl (depending on the DOC content in water 42 ) and 200 μL of SnCl 2 were successively added into the water samples to purge and trap the generated Hg 0 into a chlorinate carbon trap (CCT, 1 g weight). This approach of adding BrCl alone in filtered water released 96 ± 5% of Hg from the water samples (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…δ 202 Hg precipitation and Δ 199 Hg precipitation represent the Hg isotopic signatures in precipitation. 55 T refers to the fractional contribution of Hg II by precipitation mixed in the soil pool. Since throughfall Hg comes from rainfall Hg and additional Hg input during washout, it is assumed that the fraction of washed-out Hg contained in throughfall remains the in soil.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the physical, chemical, and biological processes that induce MDF (reported as δ 202 Hg), Hg MIF signatures, reported as Δ 199 Hg and Δ 201 Hg for odd-MIF and Δ 200 Hg for even-MIF, may specifically trace reactions and determine the contribution of distinct endmembers. For example, in forest ecosystems, Hg II in precipitation shows predominantly positive odd-MIF and even-MIF and negative values in MDF. Soil and forest biomasses display primarily negative odd-MIF and MDF, and insignificant even-MIF, ,, while atmospheric Hg 0 vapor shows negative odd-MIF, positive MDF, and slightly negative even-MIF (only around −0.05‰ in remote sites). , Given the anthropogenic emissions and biomass burning, the atmosphere in Southeast Asia showed the slightly more positive in odd-MIF , (Δ 199 Hg = −0.13 ± 0.08‰ and Δ 201 Hg = −0.12 ± 0.08‰ ) and comparable even-MIF (Δ 200 Hg = −0.04 ± 0.04‰) compared to other remote sites (Δ 199 Hg = −0.20 ± 0.08‰, Δ 201 Hg = −0.17 ± 0.10‰ and Δ 200 Hg = −0.06 ± 0.04‰ , , ). Furthermore, most physico-chemical processes preferentially remove lighter Hg isotopes and result in the heavier isotopes remaining in the residual. ,, While microbial reduction does not significantly affect odd-MIF, , abiotic oxidation by natural organic matter (NOM) in the dark gives a positive shift in odd-MIF of the residual pool of Hg 0 . , Moreover, abiotic dark reduction and organosulfur-mediated photoreduction produce a positive odd-MIF shift in the product Hg 0 , albeit the MIF is induced through different mechanisms, , whereas the organic matter-mediated photoreduction driven preferentially by O-donor groups cause a negative odd-MIF shift in the product Hg 0 . , …”
Section: Introductionmentioning
confidence: 98%